Targeted and non-targeted LC-MS analysis of microcystins in Clarias gariepinus from fishponds - Odo J. Bassey; Munyaradzi Mujuru; Mulalo I. Mutoti; Adeeyo Adeyemi; Farai Dondofema; Jabulani Ray Gumbo (Emerging Contaminants)
Cyanotoxins produced by cyanobacteria are formidable threats to aquatic ecosystems and public health worldwide. The potential health risks associated with cyanotoxins from contaminated fishponds are becoming a growing concern, as cyanotoxin production has steadily increased over time in these aquatic environments. Therefore, this study aims to utilize targeted and non-targeted Liquid Chromatography Mass Spectrometer (LC-MS) analytical methods to detect cyanotoxins in catfish (Clarias gariepinus) tissue harvested from fishponds. For detecting cyanotoxins in fish tissue utilizing the non-targeted approach, high-resolution MS/MS spectra data obtained from the analysis were converted to mzML format, analyzed with the Global Natural Product Social (GNPS) Library and CANOPUS annotations for LEVEL 3 metabolite identification, and visualized as a molecular network in Cytoscape. Regarding the targeted method, the toxin identification and quantification were achieved by comparing samples spiked with known concentrations of MC-RR and YR to an authentic toxin standard. The results of the target analysis showed that microcystin variant MC-RR was not detected in the fish tissue. The MC-YR variant was detected in the intestines and gills of Clarias gariepinus at concentrations of 13.2–10.6 μg/g and 1.5–13.9 μg/g, respectively. The muscle tissues across all fish ponds showed MC-YR concentrations between 10.5 and 16.06 μg/g. The highest concentration of MC-YR was found in the liver tissue in pond 6 (20.9 μg/g). The untargeted LC-MS method led to the identification of a larger number of cyanometabolites in the fish tissue, such as aeruginosins, anabaenopeptins, microginins. Non-toxic secondary metabolites like octadecadienoic acid, while phosphocholine (PC), ethanesulfonic acid, pheophorbide A, microcolins, cholic acid, phenylalanine, amyl amine and phosphocholine (PC), triglyceride (TG), phosphocholine (PC) and sulfonic acid derieved from cyanobacteria, fish and anthropogenic sources were also detected in the fish tissues. The non-targeted analysis facilitates the identification of both unexpected and unknown compounds.